Coping with Hostile Discrimination: The Roles of Self-Advocacy, Positive Psychology, and Unconscious Bias Training in Higher Education - Tabish Nawab (iRASD Journal of Management)
The research on Coping with Hostile Discrimination through Self-Advocacy, Positive Psychology in Higher Education, and Unconscious-Bias Training mainly emphasizes on encountering issues related to hostile Discrimination leads to the development of negative feelings in the minds of female students, such as self-doubt due to which their aspirations related to careers also get negatively impacted. There is a lack of research studies regarding the importance of self-advocacy for dealing with the problem of hostile Discrimination. Moreover, in the previous empirical studies, the concept of unconscious bias training is also lacking, due to which their role in dealing with the pertinent issue is not clear. However, the concept of positive psychology has been referred to in the previous literature for dealing with hostile Discrimination. Hostile Discrimination leads to negative experiences in women's lives, such as the symptoms of depression and anxiety, along with reduced self-esteem in them. To conduct this research, a quantitative based study has been used. The sample size has been set at 345, and a margin for blank questionnaires has also been established. There were 320 fully completed questionnaires submitted by the respondents, which helped with the analysis and production of the results. This study has chosen a conventional sample size, aiding in reliable data. After the data collection and analysis, results indicated a significant relationship between positive psychology in higher education and hostile Discrimination. Whereas unconscious-bias training insignificantly moderates the relationship between self-advocacy and hostile Discrimination. The mediating impact of self-advocacy between positive psychology in higher education and hostile Discrimination was also significant. Apart from increasing the knowledge of the constructs under study, the present research has also been effective in practical implications. The present study has encouraged the management of various universities to take important measures to promote positive psychology in higher education. Fewer resources have forced the present study to focus only on Chinese universities. Future researchers could overcome this by integrating the universities from developed countries in the context of the present study.